Peran Sir Thomas Stamford Raffles Dalam Sistem Pajak Bumi di Pulau Jawa Tahun 1811-1816 - Setyawan, Yusup Hari (KARMAWIBANGGA Historical Studies Journal, 2020)
This study aims to determine: 1) the background of Raffles in implementing the landrent system, 2) how the implementation of landrents 3) the impact after the implementation of landrents in Java in 1811-1816. This study uses a literature research method, in approaching events in the past so that historical events can be explained chronologically. The steps in this research are collecting data sources, criticizing both external and internal sources, continued with interpretation, and historiography. The results showed (1) the background of landrents replacing the forced cultivation system in Java was implemented inspired by the British experience in India. (2) The landrent system can be implemented if it can control the territory, either through diplomacy or a ceasefire to control the territory so that the system works, the landrent system was initially implemented per village, in 1814 it was changed to an individual tax system which actually made it worse, especially for farmers. (3) For the UK, the landrent system was implemented without responsibility, inconsistency in implementing the rules. For the island of Java, the implementation of the traffic rules running on the left, adopted from England, the crime rate decreased, paying attention to culture, Javanese literature, historical heritage. When the Dutch returned, the landrent system continued until 1830.